Measuring Ecuador's Economic and Political Uncertainty Index using Google Trends - Yaselga Alvarado, Emanuel Daniel (2024)
The measurement of uncertainty in a context of constant change is of paramount importance for informed decision-making, given its significant impact on investment, consumption, credit, and the financial stability of countries. This study employs Google Trends data and advanced statistical techniques to develop a political and economic uncertainty index for Ecuador, covering the period from 2004 to 2023. The proposed index effectively captures key moments of substantial instability in the country, including the overthrow of former President Lucio Gutiérrez, the declaration of default on external debt, the 30-S political crisis, the April 2016 earthquake, national strikes, and the COVID-19 pandemic. Furthermore, the index is correlated with other uncertainty measures, including the Emerging Markets Bond Index (EMBI), the Volatility Index (VIX), and oil prices. This index offers a real-time perspective on the evolution of uncertainty in Ecuador, which may prove valuable in anticipating the evolution of relevant macroeconomic variables such as consumption and investment.